12. EFFICIENCY TREATMENT OF HYPOTENSION AFTER SPINAL ANESTHESIA WITH PHENYLEPHRINE AND EPHEDRINE IN CAESAREAN SECTION (Vietnam Journal of Community Medicine, 2023)
Objectives: To compare the results of treatment of hypotension after spinal anesthesia between Phenylephrine and Ephedrine in women undergoing cesarean section. Subjects and methods: A prospective, controlled study on 63 women with indications for elective cesarean section under spinal anesthesia treated with Phenylephrine or Ephedrine at Giong Rieng District Health Center from January 2022 to September 2022. Results: After spinal anesthesia, blood pressure tended to decrease. After taking vasopressors, blood pressure increase was not different between the two groups. Following administration of Phenylephrine resulted in a sharper decrease in heart rate to approximately approximating baseline heart rate, while Ephrine did not alter heart rate significantly and was more stable. Cardiac output was significantly reduced in the phenylephrine group and increased in the ephedrine group. Phenylephrine caused more bradycardia than Ephedrine. Phenylephrine causes nausea and vomiting less than Ephedrine. Phenylephrine caused bradycardia more than Ephedrine, Phenylephrine caused nausea, vomiting less than Ephedrine. Conclusion: Phenylephrine had a strong reduction in heart rate. Ephrine did not change heart rate significantly. Cardiac output decreased in the phenylephrine group and increased in the ephedrine group.
Keywords: Ephedrine, Phenylephrine, spinal anesthesia, pregnant women.